Net Errors and Omissions Account Overview: Analysis of Selected Countries (1980-2018) - Suna Şahin (İktisat Politikası Araştırmaları Dergisi)
Not many analyses have been conducted on net errors and omissions in publications on Economics which is relevant to the origins of net errors and omissions and their effects on the balance of payments. There is no clarified answer to indicate the degree to which errors and omissions are acceptable. Each country has its characteristics, and it is tough to generalize the reasons behind the balance of payment mismatches. This research intends to study the relationship between selected countries’ (India, Singapore, Malaysia, United States, Uruguay, Philippines) balance of payment accounts ‘net errors and Omissions’ account of macroeconomic variables (GDP, trade volume considered as import and export figures) in the years of 1980-2018. The data for this study were collected from the World Bank and IMF international financial statistics and the selected countries’ annual data. In the study, panel data analysis was preferred after stasis analysis of the data. According to the results obtained, while trade volüme harms net errors and omissions, the increases in GDP are being affected positively in that direction. The inconsistencies are often unknown, although in some cases, explanations that require a review of statistics emerge later. Timing gaps, insufficient coverage, or methodological issues can cause imbalances. By finding the reason for the existence of the net error and omissions account, that is, its source, the quality of the balance of payments statistics can be further improved. Data sources should be chosen well, and laws and penal policies should be clearly stated to avoid problems.